2014
DOI: 10.1002/chem.201404428
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular Engineering of Oligothiophene Nanorods without Insulators: Hierarchical Association of Rosettes and Photovoltaic Properties

Abstract: Supramolecular rosettes of oligothiophenes that do not bear long aliphatic tails have been designed as semiconducting nanomaterials for solution-processable bulk heterojunction solar cells. The rosettes consist of six barbiturated thienyl[oligo(hexylthiophene)] units (Bar-T-hTn ; n=3,4,5) aggregated by multiple hydrogen bonds, which have been directly visualized by scanning tunneling microscopy (STM) at a solid-liquid interface. (1) H NMR spectroscopy in [D8 ]toluene showed that Bar-T-hTn exists as a mixture o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
43
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 111 publications
4
43
1
Order By: Relevance
“…3 Thus, enormous supramolecular insight into how molecular aggregation can be controlled in solution as well as in the bulk state, provided by a myriad of research examples, must contribute largely to this advanced research field. This self-assembly pathway occurred in the presence of PC 61 BM ( [6,6]-phenyl-C 61 -butyric acid methyl ester), and the resulting p-n blend film showed a power conversion efficiency (PCE) of 2.1% in the BHJ-OPV device under optimized conditions. 5 As a promising supramolecular design for hydrogen-bonding semiconductors applicable to the organic photovoltaic application, we have recently developed barbituric acid-functionalized oligothiophenes, wherein solubilizing short alkyl chains are grafted onto the p-conjugated backbone.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…3 Thus, enormous supramolecular insight into how molecular aggregation can be controlled in solution as well as in the bulk state, provided by a myriad of research examples, must contribute largely to this advanced research field. This self-assembly pathway occurred in the presence of PC 61 BM ( [6,6]-phenyl-C 61 -butyric acid methyl ester), and the resulting p-n blend film showed a power conversion efficiency (PCE) of 2.1% in the BHJ-OPV device under optimized conditions. 5 As a promising supramolecular design for hydrogen-bonding semiconductors applicable to the organic photovoltaic application, we have recently developed barbituric acid-functionalized oligothiophenes, wherein solubilizing short alkyl chains are grafted onto the p-conjugated backbone.…”
mentioning
confidence: 99%
“…S6, ESI †). 9 In our previous studies, 6 we reported BHJ solar cells of 1:PC 61 BM, whose active layers were prepared by using a solvent mixture of chloroform and toluene (1 : 1 v/v). The increased absorption intensity in the lower wavelength region is ascribable to the contribution of BDT units.…”
mentioning
confidence: 99%
“…Based on these observations, the competing formation of tapes in the supramolecular polymerization process should be disregarded, and it should accordingly be negligible for the pathway complexity observed for 1 . Moreover, the formation of diverse geometrical rosette isomers should be taken into account, the interconversion of which requires the dissociation of hydrogen bonds (Figure S25 in the Supporting Information) . The high degrees of internal order in SP 1 and SP 2 , evident from the 2D XRD analyses, indicates that the constituent molecules are packed within the supramolecular polymers as specific rosette isomers.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover,t he formation of diverse geometricalr osette isomers should be taken into account,t he interconversion of whichr equires the dissociation of hydrogenb onds (FigureS25 in the Supporting Information). [36] The high degrees of internal order in SP 1 and SP 2 ,e vident from the 2D XRD analyses, indicates that the constituent molecules are packed within the supramolecular polymers as specific rosette isomers. However,i ft he formation of diverser osette isomersw as part of the supramolecular polymerization process, pathway complexity should be observed for 1 and 2.T he fact that pathway complexity was observede xclusively for 1 suggests that the origin of kinetic behavior should be considered separately from the formation of competing hydrogen-bonded aggregates.…”
Section: Pathway Complexity In the Supramolecular Polymerizationmentioning
confidence: 97%
“…23 An alternative approach towards such multi-arm π-conjugated structures would be supramolecular macrocyclization (supermacrocyclization) of π-conjugated building blocks using directional noncovalent interactions such as hydrogen-bonding. [24][25][26][27][28][29] By using this approach, we may obtain a complex architecture of one-dimensionally stacked supermacrocyclic π-conjugated systems with a high degree of internal order.…”
Section: Introductionmentioning
confidence: 99%